ANALISIS PENGARUH FREE CASH FLOW, ASSETS GROWTH, MARKET TO BOOK VALUE, PROFITABILITY DAN DEBT TO EQUITY RATIO TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Yang Tergabung Dalam Indeks LQ-45 di Bursa Efek Indonesia Periode 2011-2015) - Putra, Oktommy; Mahfud, Mohammad Kholiq (Diponegoro Journal of Management, 2017)
This research aims to analyze the influence of Free Cash Flow, Assets Growth, Market to Book Value, Profitability and Debt to Equity Ratio to Dividend Payout Ratio on the company which group in the LQ-45 index in Indonesian Stock Exchange in period 2011-2015.Research population used company in LQ-45 index in Indonesian Stock Exchange in period 2011-2015. Taken samples of the all purpose 22 companies by using purposive sampling method. The data used in this research were obtained from the Indonesian Capital Market Directory (ICMD) 2011-2015, IDX Annual Report, and www.idx.co.id. Analysis technique used Ordinary Least Square Regression (OLS), statistical t-test, f-test, and classic assumption test that includes a test of normality test, multicollinearity test, autucorrelation test, and heteroskedastisitas test. The result of the research are independent variables simultaneously (F test) effect on Dividend Payout Ratio with a significance level of 0.000. While partially (t test) showed that the variable Free Cash Flow and Return On Assets have positive and significant effect on Dividend Payout Ratio. Variable Assets Growtth and Debt to Equity Ratio have negative and significant effect on Dividend Payout Ratio. Market to Book Value has negative and not significant effect on Dividend Payout Ratio. Adjusted R2 is 0,458 wahich means that the ability of the five independent variables can explain Dividend Payout Ratio amounted to 45,8%, while the rest is explained by other factors.